Phylogenetic position of whitefish Coregonus lavaretus (L.) from Teletskoye Lake (Siberia) based on complete mitochondrial DNA - Solovyev, Mikhail M.; Bochkarev, Nickolay A.; Oreshkova, N. V.; Kashinskaya, Elena N.; Simonov, Evgeniy P. (Russian Journal of Genetics, 2022)
The taxonomy of the European whitefish species complex Coregonus lavaretus (L.) is extremely intricate. Owing to wide distribution from Central Europe to water bodies in Chukotka and high biological plasticity, many forms with different taxonomic status have been described. Teletskoye Lake is inhabited by two endemic whitefishes: Pravdin's whitefish Coregonus lavaretus pravdinellus and Teletskoye whitefish C. smitti. Previously, a total of 106 mitogenomes of whitefishes from the C. lavaretus complex from different populations of the Baltic and North seas were sequenced; however, there are no such data for whitefishes from Siberia. We obtain the mitochondrial genomes of C. smitti and C. l. pravdinellus, 16 738 bp in length, with high coverage. The mitogenomes differ in 46 positions (0.27%). Comparative analysis of C. lavaretus mitogenomes from water bodies of Europe and Teletskoye Lake confirms the common origin of the populations from the eastern part of the Baltic Sea and water bodies of Siberia. In addition, analysis of the complete mitogenomes of C. smitti and C. l. pravdinellus does not confirm their different taxonomic status, at least on the basis of mtDNA.